Electrode composite material, preparation method thereof and lithium ion battery

By parasitizing nano-manganese lithium manganese phosphate on the surface or pores of lithium iron phosphate and installing a carbon cladding layer to form an electrode composite material, the problem of difficult processing and low compaction density of manganese lithium phosphate after nano-nanoization is solved, which is significantly Improves the performance of lithium-ion batteries.

CN119419263APending Publication Date: 2025-02-11广州融捷能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411503150.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing lithium manganese phosphate materials are difficult to process after nano-nanification and have low compaction density, which limits their large-scale application.

Method used

The electrode composite material is formed by parasitizing nano lithium manganese phosphate in the surface or pores of lithium iron phosphate and providing a carbon cladding layer on both surfaces. The mass ratio of this material is lithium manganese phosphate: (1-50): (99-50) to improve its electron and ion conduction properties.

Benefits of technology

It solves the problems of difficulty in processing and dispersion and low compaction density in nanomanganese phosphate, significantly improves its electron conduction and ion diffusion rates, and improves the low-temperature performance, rate performance and energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005103107550000101
    Figure BDA0005103107550000101
Patent Text Reader

Abstract

The invention belongs to the technical field of battery manufacturing, and particularly relates to an electrode composite material and a preparation method thereof and a lithium ion battery, the electrode composite material comprises lithium iron phosphate and lithium manganese phosphate, the lithium manganese phosphate is attached to the surface of the lithium iron phosphate and / or embedded into gaps of lithium iron phosphate particles, and carbon coating layers are arranged on the surfaces of the lithium iron phosphate and the lithium manganese phosphate; the mass ratio of the lithium manganese phosphate to the lithium iron phosphate is (1-50): (99-50). According to the invention, the electron and ion conduction performance is improved through nanocrystallization of lithium manganese phosphate, and the problems of electron conduction and ion diffusion rate of lithium manganese phosphate are greatly improved. And then the nanometer lithium manganese phosphate is parasitized to the surfaces or pores of the lithium iron phosphate particles, so that the problems of difficult processing and dispersion of the nanometer lithium manganese phosphate and low compaction density are solved. The lithium ion battery is prepared from the electrode composite material, so that the low-temperature performance, the rate capability and the energy density of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery manufacturing, and in particular relates to an electrode composite material and a preparation method thereof and a lithium ion battery. Background Art

[0002] Lithium-ion battery is a secondary battery system that uses two different lithium-intercalation compounds that can reversibly intercalate and deintercalate lithium ions as positive and negative electrodes. With its advantages of high specific capacity, long cycle life, and low self-discharge, it is widely used in mobile phones, portable computers, camcorders, cameras, electric vehicles, energy storage and other fields. Among them, lithium iron phosphate is used in pure electric buses, energy storage and other fields due to its high safety performance, good cycle life and environmental friendliness. Lithium manganese phosphate has a high operating voltage and an energy density 20% higher than lithium iron phosphate. It is environmentally friendly, but its poor electronic and ionic conductivity limits its application.

[0003] In order to improve the electronic and ion conductivity of existing lithium manganese phosphate materials, carbon coating and nano-sizing are usually used to improve their electrical properties. Although the electrical properties of materials can be greatly improved after nano-sizing, it is easy to cause uneven dispersion in the subsequent processing process, which ultimately leads to uneven surface density of the prepared pole pieces, large differences in internal resistance at different sites, and low compaction density, thus limiting its large-scale application. New process technology and material design are needed to improve it to adapt to actual production and use. Summary of the invention

[0004] The purpose of the present invention is to provide an electrode composite material and a preparation method thereof in view of the deficiencies in the prior art, and to solve the problems of difficult processing and low compaction density of nano-manganese lithium phosphate by parasitizing nano-manganese lithium phosphate on the surface or in the pores of lithium iron phosphate.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] An electrode composite material, comprising lithium iron phosphate and lithium manganese phosphate, wherein the lithium manganese phosphate is attached to the surface of the lithium iron phosphate and / or embedded in the gaps between the lithium iron phosphate particles, and the surfaces of the lithium iron phosphate and the lithium manganese phosphate are both provided with a carbon coating layer; the mass ratio of the lithium manganese phosphate to the lithium iron phosphate is (1-50):(99-50). Specifically, the mass ratio of the lithium manganese phosphate to the lithium iron phosphate is 50:50, 40:60, 35:65, 30:70, 25:75, 20:80, 10:90, 5:95 and 1:99, etc.

[0007] Preferably, the primary particle size of the lithium iron phosphate is 100-2000nm, and / or the primary particle size of the lithium manganese phosphate is 10-200nm. Specifically, the primary particle size of the lithium iron phosphate is 100nm, 200nm, 300nm, 500nm, 800nm, 1000nm, 1500nm, 1750nm and 2000nm, etc. The primary particle size of the lithium manganese phosphate is 10nm, 20nm, 40nm, 60nm, 80nm, 100nm, 150nm and 200nm, etc.

[0008] Preferably, the thickness of the carbon coating layer is 0.5-10 nm. Specifically, the thickness of the carbon coating layer is 0.5 nm, 1 nm, 2 nm, 3 nm, 5 nm, 8 nm, 10 nm, etc.

[0009] A method for preparing an electrode composite material comprises the following steps:

[0010] Step 1: Mix a carbon source, a dopant, an iron source, a first phosphorus source and a first lithium source to obtain a mixed material, wherein the added mass of the carbon source is 4-10% of the total mass of the iron source, the first phosphorus source and the first lithium source; configure the mixed material into a mixed water slurry with a solid content of 30-60%; and perform a sanding treatment on the mixed water slurry to obtain a first precursor slurry;

[0011] Step 2: spray drying the first precursor slurry in step 1 to obtain a first precursor powder, and heat treating the first precursor powder at a first preset temperature under an inert atmosphere to obtain lithium iron phosphate;

[0012] Step 3: The lithium iron phosphate of step 2 is mixed with a carbon source, a dopant, a manganese source, a second phosphorus source and a second lithium source to obtain a mixed material, wherein the added mass of the carbon source is 4-10% of the total mass of the lithium iron phosphate, the manganese source, the second phosphorus source and the second lithium source, and the mixed material is configured into a mixed water slurry with a solid content of 30-60%, and a second precursor slurry is obtained by sand grinding.

[0013] Step 4: spray-dry the second precursor slurry obtained in step 3 to obtain a second precursor powder, and heat-treat the second precursor powder at a second preset temperature under the protection of an inert atmosphere to obtain an electrode composite material.

[0014] Preferably, the carbon source comprises a combination of one or more of graphene, starch, sucrose, glucose, polyethylene glycol, polyvinyl alcohol and polyvinyl pyrrolidone.

[0015] Preferably, the dopant includes at least one of ammonium metavanadate, titanium dioxide, niobium pentoxide and magnesium oxide.

[0016] Preferably, the iron source in step 1 comprises at least one of lithium iron phosphate, iron oxide and ferrous oxalate;

[0017] The manganese source in step 3 includes at least one of manganese carbonate, manganese sulfate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese chloride and manganese nitrate.

[0018] Preferably, in step 1, the first phosphorus source includes at least one of iron phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate and lithium phosphate;

[0019] In step 3, the second phosphorus source includes at least one of lithium dihydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate and lithium phosphate.

[0020] Preferably, in step 1, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate and lithium dihydrogen phosphate;

[0021] In step 3, the second lithium source includes at least one of lithium hydroxide, lithium phosphate and lithium dihydrogen phosphate.

[0022] Preferably, in the mixed material in step 1, the molar ratio of Fe, P and Li is 1:(1.0-1.06):(1.0-1.1); specifically, the molar ratio can be 1:1:1, 1:1.01:1.02, 1:1.02:1.04, 1:1.04:1.06 and 1:1.06:1.1, etc.

[0023] In the mixed material described in step 3, the molar ratio of Mn, P and Li is 1:(1.0-1.06):(1.0-1.1). Specifically, the molar ratio can be 1:1:1, 1:1.01:1.02, 1:1.02:1.04, 1:1.04:1.06 and 1:1.06:1.1, etc.

[0024] Preferably, the particle size D50 of the particles in the precursor slurry in step 1 is 0.2-0.8 μm, and D90 is less than 3 μm;

[0025] The particle size D50 of the particles in the precursor slurry in step 3 is 0.4-1.0 μm, and D90 is less than 10 μm.

[0026] Preferably, in step 2, the temperature range of the first preset temperature is 500-800° C., the heating rate is 1-5° C. / min, and the treatment time is 5-10 h;

[0027] In step 4, the temperature range of the second preset temperature is 600-850° C., the heating rate is 1-5° C. / min, and the processing time is 5-10 hours.

[0028] Preferably, the gas used for the inert atmosphere protection includes at least one of nitrogen, argon and helium.

[0029] An electrode sheet comprises any one of the electrode composite materials described above.

[0030] A lithium ion battery comprises the electrode sheet as described above. Preferably, the electrode sheet is a positive electrode sheet.

[0031] Compared with the prior art, the beneficial effects of the present invention are: by nano-manganese lithium phosphate, its electronic and ion conductivity is improved, and the problems of electronic conduction and ion diffusion rate of manganese lithium phosphate are greatly improved. Then, the nano-manganese lithium phosphate is parasitized on the surface or pores of lithium iron phosphate particles, which solves the problems of difficult processing and dispersion of nano-manganese lithium phosphate and low compaction density. The above-mentioned electrode composite material is used to prepare a lithium-ion battery, which is beneficial to improve the low temperature performance, rate performance and energy density of the battery. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The technical solution of the present invention is further described below in conjunction with several preferred embodiments.

[0034] Embodiment 1:

[0035] A method for preparing an electrode composite material comprises the following steps:

[0036] Step 1: Weigh 150.8 g of iron phosphate, 3 g of ammonium phosphate and 38.5 g of lithium carbonate, 18 g of 4 wt% aqueous graphene slurry, and 16 g of polyvinyl pyrrolidone to form an aqueous slurry with a solid content of 40%, and then sand grind to D50 of 0.4 μm and D90 < 2 μm to obtain a first precursor slurry.

[0037] Step 2: Dry the first precursor slurry obtained in step 1 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried first precursor powder. Heat the first precursor powder to 600°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain lithium iron phosphate.

[0038] Step 3: Weigh 150 g of the lithium iron phosphate obtained in step 2, 17.3 g of manganese acetate, 10.7 g of lithium dihydrogen phosphate and 16 g of glucose to form an aqueous slurry with a solid content of 40%, and then sand-grind to a D50 of 0.8 μm and a D90 of <10 μm to obtain a second precursor slurry.

[0039] Step 4: Dry the second precursor slurry obtained in step 3 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried second precursor powder. Heat the second precursor powder to 750°C at a heating rate of 5°C / min for 9 hours under nitrogen protection to obtain an electrode composite material.

[0040] Preparation of lithium-ion battery: The electrode composite material prepared in this embodiment is mixed evenly with SP and PVDF in a mass ratio of 96:2:2 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet, the negative electrode sheet, and the isolation film are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and divided to obtain a lithium-ion battery.

[0041] Embodiment 2:

[0042] The difference between this embodiment and embodiment 1 is that in step 1, the slurry is sand-ground to D50 of 0.5 μm and D90 of less than 2 μm to obtain a first precursor slurry; and in step 3, the slurry is sand-ground to D50 of 0.7 μm and D90 of less than 10 μm to obtain a second precursor slurry; the rest of the operations are the same.

[0043] Embodiment 3:

[0044] The difference between this embodiment and embodiment 1 is that in step 1, the slurry is sand-ground to D50 of 0.6 μm and D90 of less than 2 μm to obtain a first precursor slurry; and in step 3, the slurry is sand-ground to D50 of 0.6 μm and D90 of less than 10 μm to obtain a second precursor slurry; the rest of the operations are the same.

[0045] Embodiment 4:

[0046] A method for preparing an electrode composite material comprises the following steps:

[0047] Step 1: Weigh 150.8 g of iron phosphate, 3 g of ammonium phosphate and 38.5 g of lithium carbonate, 18 g of 4 wt% aqueous graphene slurry, and 16 g of polyvinyl pyrrolidone to form an aqueous slurry with a solid content of 40%, and then sand grind to D50 of 0.4 μm and D90 < 2 μm to obtain a first precursor slurry.

[0048] Step 2: Dry the first precursor slurry obtained in step 1 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried first precursor powder. Heat the first precursor powder to 550°C at a heating rate of 5°C / min for 9 hours under nitrogen protection to obtain lithium iron phosphate.

[0049] Step 3: Weigh 150 g of the lithium iron phosphate obtained in step 2, 17.3 g of manganese acetate, 10.7 g of lithium dihydrogen phosphate and 16 g of glucose to form an aqueous slurry with a solid content of 40%, and then sand-grind to a D50 of 0.8 μm and a D90 of <10 μm to obtain a second precursor slurry.

[0050] Step 4: Dry the second precursor slurry obtained in step 3 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried second precursor powder. Heat the second precursor powder to 850°C at a heating rate of 5°C / min for 9 hours under nitrogen protection to obtain an electrode composite material.

[0051] Preparation of lithium-ion battery: The electrode composite material prepared in this embodiment is mixed evenly with SP and PVDF in a mass ratio of 96:2:2 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet, the negative electrode sheet, and the isolation film are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and divided to obtain a lithium-ion battery.

[0052] Embodiment 5:

[0053] The difference between this embodiment and embodiment 4 is that in step 2, the first precursor powder is heated to 650° C. at a heating rate of 5° C. / min for 9 hours under nitrogen protection to obtain lithium iron phosphate;

[0054] In step 4, the second precursor powder is heated to 650° C. at a heating rate of 5° C. / min under nitrogen protection and heat treated for 9 hours to obtain an electrode composite material; the rest of the operations are the same.

[0055] Embodiment 6:

[0056] A method for preparing an electrode composite material comprises the following steps:

[0057] Step 1: Weigh 159.7 g of iron oxide, 214 g of lithium dihydrogen phosphate, and 25 g of polyvinyl alcohol to prepare a water-based slurry with a solid content of 40%, and then sand-grind to a D50 of 0.6 μm and a D90 of <2 μm to obtain a first precursor slurry.

[0058] Step 2: Dry the first precursor slurry obtained in step 1 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried first precursor powder. Heat the first precursor powder to 700°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain lithium iron phosphate.

[0059] Step 3: Weigh 150 g of the lithium iron phosphate obtained in step 2, 75.3 g of manganese nitrate, 30.0 g of ammonium phosphate, 11.6 g of lithium phosphate and 16 g of sucrose to form an aqueous slurry with a solid content of 40%, and then sand-grind to a D50 of 0.5 μm and a D90 of <10 μm to obtain a second precursor slurry.

[0060] Step 4: Dry the second precursor slurry obtained in step 3 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried second precursor powder. Heat the second precursor powder to 750°C at a heating rate of 5°C / min under nitrogen protection for 10 hours to obtain an electrode composite material.

[0061] Preparation of lithium-ion battery: The electrode composite material prepared in this embodiment is mixed evenly with SP and PVDF in a mass ratio of 96:2:2 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet, the negative electrode sheet, and the isolation film are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and divided to obtain a lithium-ion battery.

[0062] Embodiment 7:

[0063] The difference between this embodiment and embodiment 6 is that in step 2, the first precursor powder is heated to 700° C. at a heating rate of 5° C. / min for 9 hours under nitrogen protection to obtain lithium iron phosphate;

[0064] In step 4, the second precursor powder is heated to 850° C. at a heating rate of 5° C. / min under nitrogen protection and heat treated for 9 hours to obtain an electrode composite material; the rest of the operations are the same.

[0065] Embodiment 8:

[0066] A method for preparing an electrode composite material comprises the following steps:

[0067] Step 1: Weigh 159.7 g of iron oxide, 214 g of lithium dihydrogen phosphate, and 25 g of polyvinyl alcohol to prepare a water-based slurry with a solid content of 40%, and then sand-grind to a D50 of 0.6 μm and a D90 of <2 μm to obtain a first precursor slurry.

[0068] Step 2: Dry the first precursor slurry obtained in step 1 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried first precursor powder. Heat the first precursor powder to 700°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain lithium iron phosphate.

[0069] Step 3: Weigh 150 g of the lithium iron phosphate obtained in step 2, 75.3 g of manganese nitrate, 30.0 g of ammonium phosphate, 11.6 g of lithium phosphate and 16 g of sucrose to form an aqueous slurry with a solid content of 40%, and then sand-grind to a D50 of 0.5 μm and a D90 of <10 μm to obtain a second precursor slurry.

[0070] Step 4: Dry the second precursor slurry obtained in step 3 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried second precursor powder. Heat the second precursor powder to 750°C at a heating rate of 5°C / min under nitrogen protection for 10 hours to obtain an electrode composite material.

[0071] Preparation of lithium-ion battery: The electrode composite material prepared in this embodiment is mixed evenly with SP and PVDF in a mass ratio of 96:2:2 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet, the negative electrode sheet, and the isolation film are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and divided to obtain a lithium-ion battery.

[0072] Embodiment 9:

[0073] The difference between this embodiment and embodiment 8 is that in step 2, the first precursor powder is heated to 800° C. at a heating rate of 5° C. / min for 9 hours under nitrogen protection to obtain lithium iron phosphate;

[0074] In step 4, the second precursor powder is heated to 750° C. at a heating rate of 5° C. / min under nitrogen protection and heat treated for 8 h to obtain an electrode composite material; the rest of the operations are the same.

[0075] Comparative Example 1:

[0076] A method for preparing a lithium iron phosphate material comprises the following steps:

[0077] Step 1: Weigh 150.8 g of iron phosphate, 3 g of ammonium phosphate and 38.5 g of lithium carbonate, 18 g of 4 wt% aqueous graphene slurry, and 16 g of polyvinyl pyrrolidone to prepare an aqueous slurry with a solid content of 40%, and then sand grind to D50 of 0.4 μm and D90 < 2 μm to obtain a precursor slurry.

[0078] Step 2: Dry the precursor slurry obtained in step 1 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried precursor powder. Heat the precursor powder to 600°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain lithium iron phosphate material.

[0079] Preparation of lithium-ion battery: The lithium iron phosphate material prepared in this comparative example is mixed evenly with SP and PVDF in a mass ratio of 96:2:2 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, the positive electrode sheet is obtained by roller pressing, and the prepared positive electrode sheet, negative electrode sheet and isolation film are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and capacity divided to obtain a lithium-ion battery.

[0080] Comparative Example 2:

[0081] A method for preparing a lithium manganese phosphate material comprises the following steps:

[0082] Step 1: Weigh 17.3 g of manganese acetate, 10.7 g of lithium dihydrogen phosphate and 16 g of glucose to prepare a water-based slurry with a solid content of 40%, and then sand-grind to a D50 of 0.8 μm and a D90 of <10 μm to obtain a precursor slurry.

[0083] Step 2: Dry the precursor slurry obtained in step 1 in a spray drying tower, set the spray drying inlet temperature at 250°C, and control the outlet temperature at 105°C to obtain a dried precursor powder. Heat the precursor powder to 750°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain a lithium manganese phosphate material.

[0084] Preparation of lithium-ion battery: The lithium manganese phosphate material prepared in this comparative example is mixed evenly with SP and PVDF in a mass ratio of 96:2:2 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet, the negative electrode sheet, and the isolation film are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and divided to obtain a lithium-ion battery.

[0085] The materials prepared in the above embodiments and comparative examples were assembled into secondary batteries for electrical performance testing, and the above batteries were charged and discharged at 0.1C, 0.5C, and 1C rates, and the average value was obtained for 10 cycles. The compaction density of the powder was then tested.

[0086] The corresponding test results are shown in the following table:

[0087]

[0088] As can be seen from the above table, Examples 1-9 are all batteries obtained by using an electrode composite material prepared in accordance with the present invention in which nano-lithium manganese phosphate is parasitic on the surface or in the pores of lithium iron phosphate. Comparative Example 1 is a battery obtained mainly using lithium iron phosphate as the electrode material, and Comparative Example 2 is a battery obtained mainly using lithium manganese phosphate as the electrode material.

[0089] By comparing the experimental results of Examples 1-9 and Comparative Example 1, it can be seen that the battery prepared by the present invention has a similar powder compaction density to the mainstream lithium iron phosphate battery, and in terms of 1C discharge gram capacity, the present invention has a more obvious advantage, so the overall total capacity of the prepared battery is higher and the energy density is greater.

[0090] It can be seen from the experimental results of Examples 1-9 and Comparative Example 2 that the battery prepared by the present invention has a similar discharge capacity per gram compared with a battery mainly using lithium manganese phosphate as the electrode material, but has a larger powder compaction density. The larger the compaction density, the higher the battery capacity and the better the overall performance.

[0091] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. An electrode composite material, characterized in that: It comprises lithium iron phosphate and lithium manganese phosphate, wherein the lithium manganese phosphate is attached to the surface of the lithium iron phosphate and / or embedded in the gaps between the lithium iron phosphate particles, and the surfaces of the lithium iron phosphate and the lithium manganese phosphate are both provided with a carbon coating layer; the mass ratio of the lithium manganese phosphate to the lithium iron phosphate is (1-50):(99-50).

2. The electrode composite material according to claim 1, characterized in that: The primary particle size of the lithium iron phosphate is 100-2000 nm, and / or, The primary particle size of the lithium manganese phosphate is 10-200 nm.

3. The electrode composite material according to claim 1, characterized in that: The thickness of the carbon coating layer is 0.5-10 nm.

4. A method for preparing an electrode composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Mix a carbon source, a dopant, an iron source, a first phosphorus source and a first lithium source to obtain a mixed material, wherein the added mass of the carbon source is 4-10% of the total mass of the iron source, the first phosphorus source and the first lithium source; configure the mixed material into a mixed water slurry with a solid content of 30-60%; and perform a sanding treatment on the mixed water slurry to obtain a first precursor slurry; Step 2: spray drying the first precursor slurry in step 1 to obtain a first precursor powder, and heat treating the first precursor powder at a first preset temperature under an inert atmosphere to obtain lithium iron phosphate; Step 3: The lithium iron phosphate of step 2 is mixed with a carbon source, a dopant, a manganese source, a second phosphorus source and a second lithium source to obtain a mixed material, wherein the added mass of the carbon source is 4-10% of the total mass of the lithium iron phosphate, the manganese source, the second phosphorus source and the second lithium source, and the mixed material is configured into a mixed water slurry with a solid content of 30-60%, and a second precursor slurry is obtained by sand grinding. Step 4: spray-dry the second precursor slurry obtained in step 3 to obtain a second precursor powder, and heat-treat the second precursor powder at a second preset temperature under the protection of an inert atmosphere to obtain an electrode composite material.

5. The method for preparing the electrode composite material according to claim 4, characterized in that: The carbon source comprises a combination of one or more of graphene, starch, sucrose, glucose, polyethylene glycol, polyvinyl alcohol and polyvinyl pyrrolidone; and / or, the dopant comprises at least one of ammonium metavanadate, titanium dioxide, niobium pentoxide and magnesium oxide; And / or, the iron source in step 1 includes at least one of lithium iron phosphate, iron oxide and ferrous oxalate; And / or, the manganese source in step 3 includes at least one of manganese carbonate, manganese sulfate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese chloride and manganese nitrate.

6. The method for preparing the electrode composite material according to claim 4, characterized in that: In step 1, the first phosphorus source includes at least one of iron phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate and lithium phosphate; In step 3, the second phosphorus source includes at least one of lithium dihydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate and lithium phosphate.

7. The method for preparing the electrode composite material according to claim 4, characterized in that: In step 1, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate and lithium dihydrogen phosphate; in step 3, the second lithium source includes at least one of lithium hydroxide, lithium phosphate and lithium dihydrogen phosphate.

8. The method for preparing the electrode composite material according to claim 4, characterized in that: In the mixed material described in step 1, the molar ratio of Fe, P and Li is 1:(1.0-1.06):(1.0-1.1); In the mixed material described in step 3, the molar ratio of Mn, P and Li is 1:(1.0-1.06):(1.0-1.1).

9. The method for preparing the electrode composite material according to claim 4, characterized in that: The particle size D50 of the particles in the precursor slurry in step 1 is 0.2-0.8 μm, and D90 is less than 3 μm; The particle size D50 of the particles in the precursor slurry in step 3 is 0.4-1.0 μm, and D90 is less than 10 μm.

10. A lithium ion battery, characterized in that: Comprising the electrode sheet as claimed in claim 14.